Case report: Mutation in NPPA gene as a cause of fibrotic atrial myopathy - Silva Cunha, Pedro; Antunes, Diana Oliveira; Laranjo, Sérgio; Coutinho, Ana; Abecasis, João; Oliveira, Mário Martins (Frontiers in Cardiovascular Medicine, 2023)
Early-onset atrial fibrillation (AF) can be the manifestation of a genetic atrial myopathy. Specific genetic identification of a mutation causing atrial fibrosis is relatively rare. We report a case of a young patient with an asymptomatic AF, diagnosed during a routine examination. The cardiac MRI revealed extensive atrial fibrosis, and the electrophysiology study showed extensive areas of low voltage. The genetic investigation identified a homozygous pathogenic variant in the NPPA gene in the index case and the presence of the variant in heterozygosity in both parents.